Experimental Study on Hydroelectric Energy Harvester Based on a Hybrid Qiqi and Turbine Structure - Bin Bao (MDPI AG, 2021)
The Qiqi structure design can automatically upset and spill its content once it arrives at limit capacity under vertical water flow excitation. Considering this function, the Qiqi structure has been utilized for small hydroelectric energy harvesting lately. To investigate the tradeoff between the Qiqi structure and the turbine structure for small hydroelectric energy harvesting, an energy harvester based on a hybrid Qiqi and turbine structure is proposed for vertical water flow hydroelectric applications. The hybrid structure is composed of a rectangular Qiqi structure, with two blades inserted on both sides. Self-tipping function of the hybrid Qiqi structure and working principle of the structure is investigated in detail. The proposed structure has both the advantages of low flow velocity energy harvesting of the Qiqi structure and high flow velocity energy harvesting of the turbine structure. A hydroelectric energy harvesting application using the hybrid structure is given to demonstrate that the hybrid structure had a higher rotational speed than the Qiqi structure under vertical low water flow excitation and was able to work at relatively high flow rates. Thus, the investigated hybrid structure can help small rotational hydropower achieve better energy harvesting performance and work at wide-range flow rates under vertical ultra-low water flow applications. At 600 mL/min, 902 μJ of electrical energy was charged by the investigated structure, which is six times higher than that using the Qiqi structure alone.